Small size AUVs: operation results and new mission concepts - Nuno Cruz (2004)
The number of successful missions with autonomous underwater vehicles(AUVs) has been increasing steadily during the last few years, validating thisemerging technology as an efficient tool for underwater sampling. At the sametime it has served to envisage their operation in more demanding scenarios. Thispaper presents results from environment monitoring missions with an AUV andnew mission concepts for the operation of one or multiple AUVs. These newconcepts are the natural evolution of previous work and also the response to therequirements of some of the identified scenarios. For each type of mission, solutionsfor navigation, control, coordination, and communications are presented.